The Utilization of Traditional Games for Early Childhood Development - Muhammad Usman; Nidar Yusuf (International Conference on Multidisciplinary Research, 2022)
The purpose of this research was to understand and describe the roles of traditional games in facilitating children’s development. In this modern era, many parents and teachers as early childhood educators are not aware of the importance of traditional gamesto optimize the growth and development of early childhood. In fact, traditional games are a good and affordable means for children to grow and develop. In this paper, theresearchersattempted to discuss the roles of traditional Bugis games as a medium for early childhood growth and development.This research was qualitative in nature because the researchers wanted to produce descriptive data (written or spoken) about people and observable behaviors during the play that can help the growth and development of children.To collect the data, the researchers used several instruments, namely observation, interviews, and documentation. Data multiplication was carried out based on the characteristics of the instrument. The results showed that traditional South Sulawesi Bugis games, with or without equipment, act asmedia for children's physical, social-emotional, language and cognitive development. The games becomean important means for children to socialize,learn to become a society member, andlearn to respectthe society’s rules. In the game-and-play situations, children can alsodevelopmathematical abilities and reasoning. Keywords: Traditional Bugis Games, Development, Early Childhood